Optimizing the role of social media in increasing public awareness in the utilization of zakat at Lazismu Dukun village - Fahmi Medias; Dina Maryana; Muhammad Riyzal Abdur Rahman; Ibal Afib Maulana; Rifki Hidayat; Humaid Husain As’ad (Universitas Muhammadiyah Magelang, 2023)
Lazismu in Dukun village is one of the institutions under the auspices of Lazismu Magelang Regency. The problem faced is the low contribution and awareness of the community in paying zakat. Lazismu in Dukun village created a program called